Bedrock hardness values and morphological zonation of a shore platform in South Africa. Issue 1 (2nd January 2020) - Knight, Jasper; Burningham, Helene
Abstract : Shore platforms found along rock coasts worldwide are often interpreted as wave abrasion acting on uniform bedrock surfaces. Whilst this viewpoint may apply at the macroscale, there are complex feedbacks among bedrock properties (rock type, mineralogy, rock structures), weathering and erosion processes and rates, and microtopography at the meso- to microscale. In turn, these influence wave runup, backwash processes, and the extent of wave-splash and physical, chemical, and biological weathering processes that result. This study investigates the relationships among bedrock hardness properties, microtopography, and shore platform denudation processes from a site on the Indian Ocean-facing coast of South Africa. Three shore-normal transects (45–57 m in length) were surveyed across the sandstone platform using a differential global positioning system (GPS). These data were integrated with rock surface hardness measurements along the transects taken using a Proceq Equotip instrument. Results show that platform morphology and hardness values vary considerably, corresponding to the most dominant denudation processes found at different positions in the tidal frame. The lowest hardness values (most extensive rock weathering) are found on the landward third of the platform but away from the land margin. The highest and greatest variability of hardness values are found on bedrock highs immediately above the highest astronomical tide level, in the lower third of the profile. This position suggests a dominant role of wave-splash and wetting/drying. Variations in hardness values and microtopography through the transects were used to develop an evolutionary model linking rock hardness values to specific weathering and erosion processes of the rocky shore platform.